1999
DOI: 10.1046/j.1463-1326.1999.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Lowering of circulating insulin and leptin is closely associated following weight reduction after vertical banded gastroplasty in obese women

Abstract: Reduction in insulin seems more important for reduction in leptin than lowering of BMI, suggesting a close association between leptin and insulin in obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
2
9
1
Order By: Relevance
“…Plasma leptin concentration changes have also been reported in surgically induced weight loss (after gastric bypass operation) (20, 21, 22, 23, 24). Guldstrand et al (20) have suggested that the reduction in insulin concentration is a key factor responsible for serum leptin reduction after vertical banded gastroplasty (20). Essentially similar results have been reported after biliopancreatic diversion; plasma leptin concentration decreased rapidly without correlation with BMI (22).…”
Section: Introductionmentioning
confidence: 78%
“…Plasma leptin concentration changes have also been reported in surgically induced weight loss (after gastric bypass operation) (20, 21, 22, 23, 24). Guldstrand et al (20) have suggested that the reduction in insulin concentration is a key factor responsible for serum leptin reduction after vertical banded gastroplasty (20). Essentially similar results have been reported after biliopancreatic diversion; plasma leptin concentration decreased rapidly without correlation with BMI (22).…”
Section: Introductionmentioning
confidence: 78%
“…Recently there have been numerous reports on changes in adipocytokine concentrations with diet and/or exercise interventions in obese individuals [29][30][31][32][33][34][35][36][37][38][39], but only a few reports examine these changes in individuals with type 2 diabetes. This is also one of the first controlled studies to examine the impact of weight loss on resistin levels in human beings.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss through diet alone or diet and exercise interventions results in elevations [29][30][31][32][33][34][35][36][37][38][39] or no change [35,40] in adiponectin levels and reductions in leptin levels [29][30][31][32][33][34][35][36][37][38][39] in obese healthy individuals. On the other hand, only one study to date has examined resistin levels after weight loss [41].…”
Section: Introductionmentioning
confidence: 99%
“…The same experiments were repeated at least three times. Leptin concentrations were determined with a double-antibody radioimmunoassay using rabbit anti-human leptin antibodies, 125 I-labeled human leptin as tracer, and human leptin as standard (Linco Research, St. Charles, MO) [13]. Plasma insulin concentrations were analyzed with a double-antibody radioimmunoassay technique (Linco).…”
Section: Discussionmentioning
confidence: 99%